Gut Bacterial and Lactobacilli Communities of Weaning Piglets in Response to Mannan Oligosaccharide and Sugar Beet Pulp In vitro Fermentation - Su-qin HANG; Wei-yun ZHU (Journal of Integrative Agriculture)
Microbiota in the gastrointestinal tract (GIT) of piglets during weaning transition can experience a sharp change which could result in growth reduction and diarrhea of weaned piglets. Dietary manipulations can play an important role in attenuating such changes caused by weaning stress. Therefore, ileal and colonic contents of weaned piglets were used as inocula, mannan oligosaccharide (MOS) or sugar beet pulp (SBP) was supplied as single energy sources to investigate effects of MOS or SBP on the shifts of gastro-intestinal microflora and lactobacilli populations. The universal bacteriaand lactobacilli-specific PCR/denaturing gradient gel electrophoresis (DGGE), cloning and sequencing techniques were used. DGGE profiles of the universal bacteria showed that great changes were found in the position, numbers and intensity of dominant bands after fermentation. The similarity of bacterial community between ileum and colon was increased to 85-97% by MOS or SBP treatment after fermentation from the similarity with 20% before fermentation. MOS treatment significantly increased the bacterial diversity and band number in both ileal and colonic fermentation (P<0.05). SBP treatment significantly increased the bacterial diversity and band number in colon (P<0.05). It implies that some species were enriched by the addition of MOS or SBP to increase the similarity and diversity of bacterial community in weaned piglets. Five specific bands appearing in MOS or SBP treatment group after fermentation were cloned and sequenced, the changes of species related to Prevotella and Ruminococcus were observed. Two bands related to uncultured bacterium with 98% similarity were detected by MOS or SBP treatment. However, there were no effects on the similarity, diversity index and lactobacilli species revealed by MOS or SBP treatment. These results imply that MOS or SBP could have beneficial effects on the weaning piglets by stablizing microbiota in the GIT microflora.